2016
DOI: 10.1177/0003489416672871
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infections in Major Head and Neck Surgeries Involving Pedicled Flap Reconstruction

Abstract: The SSI rate following pedicled flap surgeries was low and similar to free flap surgeries despite a significantly different population. No specific risk factors were associated with developing a pedicled flap SSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…Groups were comparable in 14 studies. Five articles showed that patients were significantly younger in the FF group compared to PF ( p < 0.05) [1014]. Gender representation was similar between both groups in the 20 studies reporting gender, as one study [15] showed fewer males in the FF group (70.8% vs 100%, p < 0.05) and another [16] showed fewer males in the PF group (88% vs 32%, p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Groups were comparable in 14 studies. Five articles showed that patients were significantly younger in the FF group compared to PF ( p < 0.05) [1014]. Gender representation was similar between both groups in the 20 studies reporting gender, as one study [15] showed fewer males in the FF group (70.8% vs 100%, p < 0.05) and another [16] showed fewer males in the PF group (88% vs 32%, p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Prior head and neck surgery was reported in 4 studies. Two studies [10, 17] found there was a lower proportion of patients who had prior head and neck surgery in the FF group compared to the PF group (32% vs 59 and 14% vs 31%, p < 0.05). One study [12] reporting the incidence of preoperative systemic disease showed a lower regrouped incidence of diabetes, cardiovascular disease and hypertension in the FF group (25% vs 83%, p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Patients undergoing clean-contaminated head and neck surgery are at risk of developing postoperative complications: surgical wound infections, fistula formation, flap dehiscence, and donor site infection, all increasing hospital stay, morbidity, and mortality [5,9]. In preparing this review, we found a wound infection rate after clean-contaminated head and neck surgery ranging between 2.5% and 64%, and polymicrobial in origin [6, 16-18, 27, 28, 35, 37-40].…”
Section: Discussionmentioning
confidence: 99%
“…Occurring in 20-50% of these patients, SSIs are associated with increased fistula formation, prolonged hospitalization, increased morbidity and mortality, and reconstruction failure, all resulting in increased healthcare costs. Therefore, the effectiveness of antibioprophylaxis (ABP) of SSIs is a topic of major interest [5,9].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of type of surgical closure, our study showed that patients with reconstruction were more likely to develop postoperative SSI. Similarly, this was reported in another study where reconstruction surgery was associated with increased risk of postoperative SSI, length of hospitalization stay (LOS), occurs in older patients who were likely to have neoadjuvant radiotherapy and methicillin-resistance staphylococcus aureus (MRSA) positive results [6,11]. We did not review the MRSA status of the patients in this study.…”
Section: Discussionmentioning
confidence: 84%